The impact of differentiation on the critical thinking of gifted readers and the evolving perspective of the fifth grade classroom teacher - Dreeszen, Judy L. (Kansas State University, 2009)
With the inception of No Child Left Behind, educators are required to ensure proficiency for all students in reading and math, but provide no incentive for developing the talents of gifted students (Gentry, 2006b). Implementing differentiation into the classroom can assist educators in providing appropriate instruction for all students and maximizing the potential of gifted learners. Differentiation modifies curriculum and instruction to meet the diverse needs of students in the classroom (Tomlinson, 1999, 2001, 2003). The purpose of this study was to document how differentiation influenced the gifted readers’ ability to think more critically and the fifth grade teacher’s perceptions of differentiation as it was implemented into the reading curriculum for all readers in her classroom. This qualitative research study was conducted in a fifth grade classroom in a rural mid-western community from October 24, 2008 to February 4, 2009. Data collection included response journals of the gifted readers, audio recordings of literature circle discussions, observations/field notes, digital voice recording of interviews with the gifted readers and the classroom teacher, teacher reflective journal, and weekly meetings. Data analysis revealed three levels of critical thinking within ten categories as outlined in the Written Response Hierarchy of Journal Critical Thinking. Advanced Level Critical Thinking included the categories of Synthesis, Character Affinity, Character Scrutiny, and Evaluative Inquiry. Intermediate Level Critical Thinking was evidenced by the categories of Inference, Image Construction, Author’s Writing Technique, and Prediction. Basic Level Critical Thinking was represented by responses in the Ambiguity and Engagement categories. The Oral Response Hierarchy of Literature Circle Critical Thinking revealed four critical thinking levels of oral response. Analytical and Probe represented Advanced Level Critical Thinking, Conjecture demonstrated Intermediate Level Critical Thinking, and Engagement provided evidence of Basic Level Critical Thinking. Advanced Level Critical Thinking was evidenced in both written and oral responses across the three stages of the study. Data analysis further revealed the teacher’s perceptions of differentiated instruction. Benefits included increase in students’ motivation, active involvement and leadership, exceeding expectations, quality of literature circle discussions, confidence in implementing differentiation with continuous support of a mentor, flexibility, and empowerment to solve problems.
Keywords: Differentiation; Gifted readers; Literature response journals; Literature circle discussions; Critical thinking; Education, Curriculum and Instruction (0727); Education, Reading (0535); Education, Special (0529)